Assessing the role of global media assistance in promoting public service broadcasting in Indonesia. Issue 2 (1st July 2020) - Masduki,
In today's globally connected society, the transformation of state-administered broadcasters into public service broadcasters (PSB) in new democracies is part of international media development projects that seek to democratize media systems following the collapse of authoritarian ideologies in the 1990s. This article traces the 'what, who, when and how' of international media assistance, with particular focus on projects that sought to transform Indonesia's state-run broadcasters into PSBs during the 2000s–2010s. Drawing on extensive library research and semi-structured interviews, this article demonstrates the role of international agencies in the promotion of public service media in post-authoritarian Indonesia. They have influenced civil societies, policy-makers and media elites and promoted a belief that an independent and public-owned media enable people to better participate in a mediated public sphere. In this manner, international agencies have influenced policy design as Indonesia has transformed its national state-owned broadcast channels from state institutions into public ones. However, this article also finds that global intervention has failed to influence the more specific elements of PSB policy and implementation. In Indonesia, global work has focused on national regulatory design, leaving implementation to local actors. Furthermore, Indonesia's PSB policy is but 'an imitative version' of PSB policies in developed western countries, lacking a detailed guide for transforming the country's state-channels into true PSBs.